Burnout in terms of work stress and workload - Ruth Hawani Friska; Tjitjik Hamidah (Universitas Mercu Buana Jakarta, 2021)
The purpose of this study was to find out the effect of work stress and workload on burnout on hospital physiotherapy health workers. Cipto Mangunkusumo. The population in this study was the health care of physiotherapy hospitals. Cipto Mangunkusumo, which numbered 50 respondents using the sampling method, is a saturated sampling technique. The data retrieval method in this study used 3 scales of measuring tools, namely: work stress, workload and burnout. The burnout scale validity test data collection consists of 27 items declared valid and 5 items declared dead, the burnout scale rehabilitation of 0.879. The work stress scale validity test consisted of 20 items declared valid and 4 items declared dead, the work stress scale rehabilitation test by 0.807. And the workload scale validity test consisted of 18 items declared valid and 6 items declared dead, the workload scale rehabilitation test of 0.822. So that the results of data retrieval methods there is an effect of work stress on burnout in hospital physiotherapy health workers. Cipto Mangunkusumo, there is an effect of workload on burnout in hospital physiotherapy health workers. Cipto Mangunkusumo and there is an effect of work stress and workload on burnout on hospital physiotherapy health workers. Cipto Mangunkusumo.